1997
DOI: 10.1902/jop.1997.68.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Regeneration by Application of Recombinant Human Bone Morphogenetic Protein‐2 to Horizontal Circumferential Defects Created by Experimental Periodontitis in Beagle Dogs

Abstract: The purpose of this study was to examine the regeneration of periodontal tissue after the application of recombinant human bone morphogenetic protein-2 (rhBMP-2) to horizontal circumferential defects created by experimental periodontitis. Twelve mandibular second premolars in 6 adult beagle dogs were subjected to experimental periodontal breakdown by placing silk ligatures around the teeth until the bone loss exceeded half of the root length. Flap surgery was then performed and the exposed cementum removed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
148
2
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(157 citation statements)
references
References 11 publications
4
148
2
3
Order By: Relevance
“…BMP2 and BMP4 are the most thoroughly investigated members of the TGF-␤ superfamily for tooth and periodontal development and regeneration 20,21) . Although BMPs are expressed in the ERM 30) , the expres- sion of BMPs following mechanical stretching was unknown.…”
Section: Apoptosismentioning
confidence: 99%
“…BMP2 and BMP4 are the most thoroughly investigated members of the TGF-␤ superfamily for tooth and periodontal development and regeneration 20,21) . Although BMPs are expressed in the ERM 30) , the expres- sion of BMPs following mechanical stretching was unknown.…”
Section: Apoptosismentioning
confidence: 99%
“…However, IBM may possibly contain some unknown factors and xenogeneic IBM restricts the clinical application of rhBMP [5,7]. Poly D, L lactic-co-glycolic acid (PLGA)/gelatin sponge complex (PGS) was developed as a new carrier of rhBMP-2 and this combination induced periodontal regeneration in dogs [8].…”
mentioning
confidence: 99%
“…36 It has been suggested that slower release of BMP-2 and more prolonged exposure could increase cementogenesis. [37][38][39] Accordingly, enhanced cementogenesis might be achieved through the slower BMP-2 release accomplished with ex vivo gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that connective tissue formation processes are the primary mechanisms for inhibition of epithelial downgrowth. 37 Despite the notable induction of mesenchymal cell differentiation by BMP-2, it has also been suggested that the transforming growth factor-b superfamily, of which BMP-2 is a member, can inhibit epithelial downgrowth. 39 Our histological assessment of the advBMP-2 group supports the idea that BMP-2 inhibits epithelial down- growth.…”
Section: Discussionmentioning
confidence: 99%